Colorectal polypectomy during insertion and withdrawal or only during withdrawal? A randomized controlled trial - Wildi, S. M.; Schoepfer, A. M.; Vavricka, S. R.; Fruehauf, H.; Safroneeva, E.; Wiegand, N.; Bauerfeind, P.; Fried, M. (Endoscopy, 2012)
Background and study aims: Removal of colorectal polyps is routinely performed during withdrawal of the endoscope. However, polyps detected during insertion of the colonoscope may be missed at withdrawal. We aimed to evaluate whether polypectomy during both insertion and withdrawal increases polyp detection and removal rates compared with polypectomy at withdrawal only, and to assess the duration of both approaches.Patients and methods: Patients were included into the study when the first polyp was detected, and randomized into two groups; in group A, polyps ≤ 10 mm in diameter were removed during insertion and withdrawal of the colonoscope, while in group B, these polyps were removed at withdrawal only. Main outcome measures were duration of colonoscopy, number of polyps detected during insertion but not recovered during withdrawal, technical ease, patient discomfort, and complications.Results: 150 patients were randomized to group A and 151 to group B. Mean (± standard deviation [SD]) duration of colonoscopy did not differ between the groups (30.8 ± 15.6 min [A] vs. 28.5 ± 13.8 min [B], P = 0.176). In group A 387 polyps (mean 2.58 per colonoscopy) were detected and removed compared with 389 polyps detected (mean 2.58 per colonoscopy) in group B of which 376 were removed (13 polyps were missed, mean size [SD] 3.2 [1.3] mm; 7.3 % of patients). Patient tolerance was similar in the two groups. Conclusions: Removal of polyps ≤ 10 mm during withdrawal only is associated with a considerable polyp miss rate. We therefore recommend that these polyps are removed during both insertion and withdrawal.